PENENTUAN RUTE OPTIMAL DISTRIBUSI AIR MINUM ISI ULANG DI GERAI AFSHEENA DENGAN MENGGUNAKAN METODE SAVING MATRIX DAN NEAREST INSERT - Habibi Siraj Aflah Hibatulloh; Suseno Suseno (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Afsheena outlet is a business engaged in the distribution of goods in the form of refillable gallons of drinking water. Currently, businesses are still using manual methods in determining the distribution route of goods. This causes ineffective routes and also has an impact on distribution costs. This research aims to apply the saving matrix method and the nearest insert algorithm to optimize the distribution route of goods at Afsheena Outlets. The saving matrix method is an economical technique to calculate distances and routes by paying attention to the carrying capacity of the vehicle, while the nearest insert algorithm can determine the order of consumer visits at the time of distribution based on the total minimum distance. The results of the study show that the saving matrix method and the nearest insert algorithm can optimize the distribution route of goods at Afsheena Outlets. This is evidenced by the decrease in total mileage by grouping 6 distribution routes from the initial route of 77.2 km and the final route of 70 km or a decrease of 9.3%. The result of the initial route distribution is Rp.3,245,066/month and the final route cost is Rp.3,182,665/month, a difference of Rp.62,401,- or a savings of 1.9%.